Determinan Kejadian Dermatitis Kontak Pada Pekerja Bengkel di Kota Kendari - La Ode Alifariki; adius kusnan; Saida Saida (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
One of the problems in occupational health is occupational diseases. Occupational disease is a disease caused by a job or work environment. Occupational disease that often occurs is contact dermatitis. Contact dermatitis is dermatitis caused by material or substance that sticks to the skin. The study results of the Indonesian Ministry of Health in 2016 for informal workers were 44.2%. Allergic contact dermatitis. Likewise, in 2017 the 2017 Profile of Worker Health Problems in Indonesia obtained 50.5% of work related to work, one of which was skin disorders of 5.3%. This study aims to determine the factors associated with the incidence of contact dermatitis in motorbike workshop workers in Kendari City 2018. This study was quantitative with cross sectional study design. The populations in this study were all The mechanics of motorcycle workshop in Kendari city in 2016, amounting to 459 people. The samples in this study were 58 people. The Results showed that, there was a relationship between long contact and symptoms of contact dermatitis with ρ value = 0.000, there was no relationship between a history of skin disease and symptoms of contact dermatitis with ρ value = 0.174, there was relationship between personal hygiene and symptoms of contact dermatitis with ρ value = 0.026, and there was a relationship between the use of PPE and symptoms of contact dermatitis with ρ value 0,003